Clinical Reasoning: A Teenage Girl With Progressive Hyperkinetic Movements, Seizures, and Encephalopathy. (3rd January 2023) - Khamis, Sonia; Mitakidou, Maria R.; Champion, Michael; Goyal, Sushma; Jones, Rachel L.; Siddiqui, Ata; Sabanathan, Saraswathy; Hedderly, Tammy; Lin, Jean-Pierre; Jungbluth, Heinz; Papandreou, Apostolos
Abstract : The "epilepsy-dyskinesia" spectrum is increasingly recognized in neurogenetic and neurometabolic conditions. It can be challenging to diagnose because of clinical and genetic heterogeneity, atypical or nonspecific presentations, and the rarity of each diagnostic entity. This is further complicated by the lack of sensitive or specific biomarkers for most nonenzymatic neurometabolic conditions. Nevertheless, clinical awareness and timely diagnosis are paramount to facilitate appropriate prognostication, counseling, and management.This report describes a case of a teenage girl who had presented at 14 months with a protracted illness manifesting as gastrointestinal upset and associated motor and cognitive regression . A choreoathetoid movement disorder, truncal ataxia, and microcephaly evolved after the acute phase. Neurometabolic and inflammatory investigations, EEG, brain MRI, muscle biopsy (including respiratory chain enzyme studies), and targeted genetic testing were unremarkable. A second distinct regression phase ensued at 14 years consisting of encephalopathy, multifocal motor seizures, absent deep tendon reflexes and worsening movements, gut dysmotility, and dysphagia. Video EEGs showed an evolving developmental and epileptic encephalopathy with multifocal seizures and nonepileptic movements. MRI of the brain revealed evolving and fluctuating patchy bihemispheric cortical changes, cerebellar atrophy with signal change, mild generalized brain volume loss, and abnormal lactate on MR spectroscopy. The article discusses the differential diagnostic approach and management options for patients presenting with neurologic regression, encephalopathy, seizures, and hyperkinetic movements. It also emphasizes the utility of next-generation sequencing in providing a rapid, efficient, cost-effective way of determining the underlying etiology of complex neurologic presentations.